Atração de miracídios de Schistosoma mansoni por hospedeiros invertebrados: comportamento de miracídios frente a girinos de Hyla fuscovaria Miracidia attraction to invertebrate hosts: miracidia behavior in the presence of Hyla fuscovaria girina - Beatriz de C. Brasio; Luiz Augusto Magalhães; Joseph Miller; José F. de Carvalho (Universidade de São Paulo, 1985)
Analisou-se a atração de miracídios de Schistosoma mansoni das linhagens BH e SJ frente a seus vetores simpátricos e alopátricos tendo-se em consideração a possibilidade da presença de substâncias quimiotáxicas emanadas dos moluscos. Estudou-se também o comportamento desses miracídios frente a girinos de Hyla fuscovaria. Foi verificado que houve atração dos miracídios pelos moluscos vetores e que essa atração foi mais evidente quando a larva era colocada frente ao seu hospedeiro simpátrico.As observações realizadas no decorrer da experiência demonstraram a presença de substâncias miraxonais emanadas pelos moluscos. Miracidia tropism to suitable hosts is a subject of much controversy. In this work, we try to determine the possible specificity of Schistosoma mansoni miracidia attraction and also the degree of this specificity. To this end an experiment was carried out to determine the probability of attraction in a given experimental set up, to H. fuscovaria girina or to one of two susceptible snail species. Two strains of S. mansoni were employed and also the corresponding snail species. A specially designed apparatus consisting of two circular glass chambers joined by an open channel was used. One of the girina or a snail was placed in one of the chambers (randomly chosen). In the channel a known number of miracidia were deposited and the count of miracidia in each of the three compartments (the two chambers and the channel) was recorded. The experiment was carried out under strong or subdued lighting. Statistical and ad-hoc exploratory data analysis have shown that: a) the miracidia, when exposed to only one species of snail, show more attraction to the sympatric snail host; b)one strain of miraciadia showed more attraction under strong lighting; the other strain behaved the opposite way, with stronger attraction under weak liht; c) the girina did not attract the miracidia; this seems to imply that sone chemiotropism is present in this phenomenon.